Common cytokine receptor gamma chain family cytokines activate MAPK, PI3K, and JAK/STAT pathways in microglia to influence Alzheimer’s Disease - Zuppe, Hannah; Reed, Erin (Frontiers in Molecular Neuroscience, 2024)
Dementia is an umbrella term used to describe deterioration of cognitive function. It is the seventh leading cause of death and is one of the major causes of dependence among older people globally. Alzheimer’s Disease (AD) contributes to approximately 60–70% of dementia cases and is characterized by the accumulation of amyloid plaques and tau tangles in the brain. Neuroinflammation is now widely accepted as another disease hallmark, playing a role in both the response to and the perpetuation of disease processes. Microglia are brain-resident immune cells that are initially effective at clearing amyloid plaques but contribute to the damaging inflammatory milieu of the brain as disease progresses. Circulating peripheral immune cells contribute to this inflammatory environment through cytokine secretion, creating a positive feedback loop with the microglia. One group of these peripherally derived cytokines acting on microglia is the common cytokine receptor γ chain family. These cytokines bind heterodimer receptors to activate three major signaling pathways: MAPK, PI3K, and JAK/STAT. This perspective will look at the mechanisms of these three pathways in microglia and highlight the future directions of this research and potential therapeutics.